Hybrid Security in the Post-Modern Era: Challenges and Responses in International Relations - Tudor, Andreea-Loredana (Acta Universitatis Danubius. Relationes Internationales, 2025)
The contemporary international system faces a diversity of security threats, in the context of an international dynamic that is in continuous change. Moreover, we can note the existence of economic interdependence, multipolarity and the acceleration of technological progress. Thus, the international society faces complex security challenges, including hybrid threats, the escalation of cyber conflicts, the intensification of geopolitical competition and the increase in vulnerabilities associated with climate crises and social instability. The transitional space between peace and war has expanded, transforming into a zone of unconventional conflict, characterized by threats such as propaganda, cyberattacks and disinformation. The asymmetric practices adopted by certain states generate an intensification of concerns at the international level, determining an acute need for cooperation between actors, in order to build a common front against hybrid threats. The concept of hybrid security has developed as a specific response to the postmodern era, aiming to combat conventional and unconventional attacks in a highly interconnected international system. This research aims to analyse, through a multidisciplinary approach, the reactions of the international community to such challenges, as well as the main instruments developed by leading global actors, such as the European Union and NATO, in managing them. The study also identifies and examines the main types of hybrid threats, approached through the lens of classical theories of international relations. Finally, the paper discusses aspects related to global governance in the context of a multipolar world and explores possible responses, both from a theoretical and applied perspective, to the stated security challenges. This approach contributes to a deeper understanding of the adaptation and resilience mechanisms of the international system in the face of new forms of hybrid conflict.